2010
DOI: 10.1177/1321103x10384200
|View full text |Cite
|
Sign up to set email alerts
|

Students’ motivation to study music: The United States of America

Abstract: ArticleResearch Studies in Music Education 32(2) 201-213 AbstractAs a part of a larger international mapping exercise to examine students' motivation to study music as compared to other school subjects, this article draws upon data from a sample of 3037 students in the USA to observe perceptions of values, competence and interest in music study (in school versus outside of school) among music learners and non-music learners. Students were grouped into three grade levels: (a) 6, (b) 7-9, and (c) 10-12. Music le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 11 publications
1
48
1
5
Order By: Relevance
“…Music education systems in the United States have traditionally emphasized competitive-referent achievement as a means of motivating students to practice (see Austin, 1990Austin, , 1991Hendricks, Smith, & Stanuch, 2014;McPherson & Hendricks, 2010). However, recent scholars have suggested that an overemphasis on competition in music may in fact limit the attractiveness and accessibility of music to youth (Isbell & Stanley, 2011;McPherson & Hendricks, 2010;Radocy, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Music education systems in the United States have traditionally emphasized competitive-referent achievement as a means of motivating students to practice (see Austin, 1990Austin, , 1991Hendricks, Smith, & Stanuch, 2014;McPherson & Hendricks, 2010). However, recent scholars have suggested that an overemphasis on competition in music may in fact limit the attractiveness and accessibility of music to youth (Isbell & Stanley, 2011;McPherson & Hendricks, 2010;Radocy, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent scholars have suggested that an overemphasis on competition in music may in fact limit the attractiveness and accessibility of music to youth (Isbell & Stanley, 2011;McPherson & Hendricks, 2010;Radocy, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…McPherson and Hendricks (2010) discovered a significant rise in interest toward school music for U.S. students at the secondary level, which comes at a time when many music students have the opportunity to participate in their school jazz ensemble. These results reinforce the previous research that suggests acquisition of jazz theory knowledge (Ciorba, 2009;Madura, 1992) and proper motivation (Asmus, 1985(Asmus, , 1986a(Asmus, , 1986b(Asmus, , 1994Asmus & Harrison, 1990;McPherson & Hendricks, 2010) can be of essential importance when teaching and learning jazz improvisation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of that study not only supported the hypothesized influence of jazz theory knowledge on improvisation achievement but also demonstrated the significant influence of both motivation and academic achievement on jazz theory knowledge. Research in the area of motivation toward music learning continually has revealed that motivation plays a critical role in the learning process (Asmus, 1985(Asmus, , 1986a(Asmus, , 1986b(Asmus, , 1994Asmus & Harrison, 1990;Austin, 1988;Austin & Vispoel, 1992;Legette, 1993;McPherson & Hendricks, 2010;Miksza, 2009;Schmidt, 2005; Sichivista, 2004). If a student is not motivated to study music, the learning process most likely will be unsuccessful (Asmus, 1994).…”
mentioning
confidence: 99%
“…Such intrinsic motivation leads to lifelong learning, an attitude that must be cultivated to counter general student apathy [12]. For adolescents, extrinsic motivation can be greatly influenced by peer approval and social identification [11]. By allowing students to express themselves and create projects closely tied to their own interests, many of the negative associations of traditional music programs could be alleviated.…”
Section: Key Factors In Facilitating Creative Thoughtmentioning
confidence: 99%